The learning trajectory of social arithmetic using PMRI approach with a zakat maal context - Lukmana, Deanisa Noviana; Rahmawati, Mika Desrifa Dwi; Mardhiyah, Nida (Pi Radian: Journal of Mathematics Education, 2023)
This research aims to improve students' understanding of social arithmetic material and its role in the real world. This research uses a design research method that designs social arithmetic material with the PMRI approach and Learning Trajectory for class VII using the concept of zakat maal. The results of the study found that learning social arithmetic in the context of zakat helps students to relate arithmetic concepts to the real world and understand the role of arithmetic in zakat management. Students can see how arithmetic is used in calculating the amount of zakat, distributing zakat to mustahik, and managing zakat funds effectively.